2023
DOI: 10.1101/2023.01.28.526014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myeloperoxidase promotes a tumorigenic microenvironment in non-small cell lung cancer

Abstract: Myeloperoxidase (MPO) is a heme peroxidase that is mainly expressed and secreted by neutrophils. The role of MPO in inflammatory diseases has been highlighted in recent years, but its role in tumor development remains unclear. Therefore, we investigated the role of MPO in non-small cell lung cancer (NSCLC). In silico analysis revealed a survival benefit in patients with NSCLC and low MPO expression. Furthermore, a syngeneic tumor model using MPO knockout (KO) mice revealed that mice lacking MPO had lower tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Previous studies in our laboratory have shown that MPO-deficient mice (MPO KO; C57BL/6 MPO −/− ) have up to a 40% reduction in tumour size compared to MPO wild-type mice (C57BL/6 MPO +/+ ) [ 29 ]. To further understand the role of MPO in the setting of lung cancer, we aimed to investigate whether MPO can alter the function of tumour cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies in our laboratory have shown that MPO-deficient mice (MPO KO; C57BL/6 MPO −/− ) have up to a 40% reduction in tumour size compared to MPO wild-type mice (C57BL/6 MPO +/+ ) [ 29 ]. To further understand the role of MPO in the setting of lung cancer, we aimed to investigate whether MPO can alter the function of tumour cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Low MPO expression has been linked to a reduced risk of developing lung cancer [ 28 ]. Moreover, different studies have indicated a pro-tumorigenic function of MPO in the lung TME [ 29 , 40 ]. Recent studies from our laboratory showed that tumour-bearing MPO knock-out mice (MPO KO) had reduced tumour growth when compared to their wild-type (WT) littermates [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations